Real Time Implementation of Variable Step Size Based P&O MPPT for PV Systems Based on dSPACE - K. Muthukumar; T.S. Anandhi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2016)
Nowadays Solar energy is an important energy source due to the energy crisis and environment pollution. Maximum power point tracking (MPPT) algorithm improves the utilization efficiency of a photovoltaic systems. In this paper an improved P&O MPPT algorithm is developed and simulated using MATLAB / SIMULINK to control the DC/DC buck converter. The obtained simulink model is also verified using dspace tool. Both the simulated and experimental results are validated by also comparing them with conventional MPPT methods. The performance measures show the increase in the efficiency of PV system by the proposed model.